OSMOSIS – PUFFING SEBAGAI SUATU ALTERNATIF PROSES PENGERINGAN BUAH DAN SAYURAN - Daniel Saputera (Jurnal Keteknikan Pertanian, 2006)
Abstract A new method of drying fruits and vegetables, a combination of the osmotic drying with the CO2 puffing process, was carried out in this study. the fruits were soaked in an osmotic media, continued by puffing the product with CO2 gas and then dried using the fluidized bed dryer wich resulted in a product that resembled the volume and  shape of  a fresh product. The type of osmotic media and concentration, and the soild gain. Also the sample’s tichness had a significant effect on the water loss and solid gain. The best concentration was 50%, and the best media was sucrose. Osmotic-puffing using sugar solution had no significant effect to the ratio of bulk specific volume (BSV) between the osmotic puffing compare to without osmotic. The product treated with the solution of KCI combined with sugar had a lower BSV of puff product compared to the product soaked only with KCI. The concentration of KCI 5% gave the best BSV. The NaCI solution of  5% was also tested for osmotic-puffing dehydration of carrot which resulted in the BSV of 6.8 cm3/g. Keyword: osmotic, pufing, CO2